Choosing and using methodological search filters: searchers' views. (23rd April 2014) - Beale, Sophie; Duffy, Steven; Glanville, Julie; Lefebvre, Carol; Wright, Dianne; McCool, Rachael; Varley, Danielle; Boachie, Charles; Fraser, Cynthia; Harbour, Jenny; Smith, Lynne
Abstract Background Search filters or hedges are search strategies developed to assist information specialists and librarians to retrieve different types of evidence from bibliographic databases. The objectives of this project were to learn about searchers' filter use, how searchers choose search filters and what information they would like to receive to inform their choices. Methods Interviews with information specialists working in, or for, the National Institute for Health and Care Excellence (NICE) were conducted. An online questionnaire survey was also conducted and advertised via a range of email lists. Results Sixteen interviews were undertaken and 90 completed questionnaires were received. The use of search filters tends to be linked to reducing a large amount of literature, introducing focus and assisting with searches that are based on a single study type. Respondents use numerous ways to identify search filters and can find choosing between different filters problematic because of knowledge gaps and lack of time. Conclusions Search filters are used mainly for reducing large result sets (introducing focus) and assisting with searches focused on a single study type. Features that would help with choosing filters include making information about filters less technical, offering ratings and providing more detail about filter validation strategies and filter provenance.